Diversity and distribution of molluscs in the high shore mangroves of Peninsular Malaysia with emphasis on the family ellobiidae / Mohamad Hanif Ismail - Mohamad Hanif , Ismail (2019)
The high shore mangrove or the dry land forest with its fauna is first and most vulnerable part of the mangrove ecosystem to be subjected to anthropogenic disturbance such as land conversion for aquaculture, agriculture, housing schemes, infrastructure and harbour facilities. This study aimed to document the diversity, occurrence and distribution of high shore molluscs in Peninsular Malaysia, the Ellobiidae, in order to assess their vulnerability to human disturbance. One major objective of the study was to construct a taxonomic key to the Ellobiidae of the high shore mangroves. Field surveys and samplings of high shore molluscs were carried out at ten locations of mangroves in Peninsular Malaysia from September 2013 to April 2015, where the mangroves ranged from disturbed, mixed to pristine. At Matang Mangrove Forest Reserve, field visits were made monthly from February 2014 until May 2015 (16 months); here, high-shore molluscs were sampled on a permanent sampling plot, as well as sampling molluscs at the lower shore. Fifty-four species and 17 families of molluscs were recorded from the ten sampling locations throughout the peninsula’s coastline. A total of 19 molluscs species from eight genera and five families, were recorded for the first time in Peninsular Malaysia. One species, Ellobium scheepmakeri, once thought to be locally extinct, is rediscovered in Bukit Belimbing (Kuala Selangor) in Selangor. Most of the high-shore species were from the family Ellobiidae (15 species, 6 genera), and Cyrenidae (2 species, 1 genus). Taxonomic keys to the species of Auriculastra, Cassidula, Cylindrotis, Ellobium, Melampus, Laemodonta and Pythia are constructed for the Ellobiidae. Correspondence analysis of mollusc distribution in the Matang mangrove indicates that while the intertidal molluscs display the typical zonation pattern that can be ascribed to tidal immersion or emersion, various species also display microhabitat preference (e.g. living on foliage, tree trunks, fallen logs). In general, the high-shore ellobiids tend to live on higher places and/or cluster together (especially E. aurismidae) and are present throughout the year. Since ellobiids are adapted to live on the high shore margins of mangrove forests, they can be useful bioindicators of anthropogenic impacts on the mangrove and other coastal ecosystems.